2005
DOI: 10.1002/j.1467-8438.2005.tb00659.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychoanalytic Ideas and Systemic Family Therapy: Revisiting the Question ‘Why Bother?’

Abstract: Despite a history of ambivalence, systemic family therapy has shown signs of a re‐engagement with psychoanalytic ideas over the past fifteen years. This article revisits the question: why bother with psychoanalytic ideas in family therapy? A brief description of work with a family is used to prompt the theory discussion, which identifies and discusses particular ideas from psychoanalysis that are potentially very useful for everyday family therapy practice. These ideas are the unconscious and unconscious commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 30 publications
0
29
0
Order By: Relevance
“…For many of us, the defining task of our therapeutic practice is a quest to help our clients make more congruent meanings out of the events of their lives. At our most optimistic, we seek to help our clients find their way to piecing together stories of tragedy into narratives and sequences that make life, at best, more liveable and, at worst, slightly less frightening (Byng-Hall, 1997;Gibney, 1999;Flaskas, 2002bFlaskas, , 2005Pocock, 2005;Dallos, 2006aDallos, , 2006bByrne & McCarthy, 2007;Flaskas, 2007a). It would make sense, then, that we also come to try to find our way in making sense of our clients, and their relating to us, in a form that serves this admirable (Rober, 1999;Flaskas, 2002aFlaskas, , pp.…”
Section: The Search For Meaningmentioning
confidence: 98%
“…For many of us, the defining task of our therapeutic practice is a quest to help our clients make more congruent meanings out of the events of their lives. At our most optimistic, we seek to help our clients find their way to piecing together stories of tragedy into narratives and sequences that make life, at best, more liveable and, at worst, slightly less frightening (Byng-Hall, 1997;Gibney, 1999;Flaskas, 2002bFlaskas, , 2005Pocock, 2005;Dallos, 2006aDallos, , 2006bByrne & McCarthy, 2007;Flaskas, 2007a). It would make sense, then, that we also come to try to find our way in making sense of our clients, and their relating to us, in a form that serves this admirable (Rober, 1999;Flaskas, 2002aFlaskas, , pp.…”
Section: The Search For Meaningmentioning
confidence: 98%
“…Identified primarily as a field of practice, the growth of knowledge in CFT has mainly emphasized the interaction between practice and theory (Flaskas, 2005). Empirical knowledge has, at least within parts of the systemic CFT field, been met with skepticism because it was associated with experimental quantitative trials in laboratory settings that CFT clinicians did not identify with or found relevant for concrete CFT contexts (Pinsof & Wynne, 2000;Solem, Tilden, & Thuen, 2008).…”
Section: Historical and Theoretical Background For Cftmentioning
confidence: 99%
“…The Family unit's theoretical basis may most correctly be characterized as 'integrative practice' with several sources of influence (Flaskas, 2005), and the therapy methods described in the study of Lundblad and Hansson (2006) psychotherapy integration -together with eclecticism -has become the dominant approach in therapeutic practice (Lambert, Bergin, & Garfield, 2004;Larner, 2004;Roth & Fonagy, 2005).…”
Section: The Family Unit's Treatment Approachmentioning
confidence: 99%
“…Systemic ideas are about contextualizing issues and examining relationship patterns in human systems (Jenkins and Asen, 1992). While systemic ideas are those that focus on interpersonal processes and interpersonal contexts of individual experience, psychodynamic ideas focus on intrapersonal and intrapsychic processes (Flaskas, 2005a, p. 126).…”
Section: Terms and Labelsmentioning
confidence: 99%